SPECT/CT for Lymphatic Mapping of Sentinel Nodes in Early Squamous Cell Carcinoma of the Oral Cavity and Oropharynx. (25th August 2010) - Stephan K., Haerle; Sandro J., Stoeckli
Abstract : Adequate staging and treatment of the neck in squamous cell carcinoma of the oral cavity and oropharynx (OSCC) is of paramount importance. Elective neck dissection (END) of the clinical N0-neck is widely advocated as neck treatment. With regard to the prevalence of 20–40% of occult neck metastases found in the ND specimens, the majority of patients undergo surgery of the lymphatic drainage basin without therapeutic benefit. Sentinel node biopsy (SNB) has been shown to be a safe, reliable and accurate alternative treatment modality for selected patients. Using this technique, lymphatic mapping is crucial. Previous reports suggested a benefit of single photon emission computed tomography with CT (SPECT/CT) over dynamic planar lymphoscintigraphy (LS) alone. SPECT/CT allows the surgeon for better topographical orientation and delineation of sentinel lymph nodes (SLN's) against surrounding structures. Additionally, SPECT/CT has the potential to detect more SLN's which might harbour occult disease, than LS. SPECT/CT is recommended to be used routinely, although SPECT/CT is not indispensable for successful SNB.